Hétérogénéité des niveaux et rythmes des élèves : dilemmes d’enseignants du primaire en formation et titulaires dans deux contextes - Philippe Wanlin; Pascale Dessart; Marcel Crahay (Éducation et Socialisation)
This paper examines teachers’ beliefs about the dilemmas related to student level heterogeneity management. More than 900 teachers participated in two quantitative studies. The first shows the relevance of the measuring instrument when administered to Belgian teachers, population at the origin of the items collected through interviews. The second checks whether this instrument has the same psychometric power to identify these dilemmas according to the status (in training or tenure) and the country (Switzerland or Belgium) of the respondents. The results show some stability in the dilemmas with different psychometric power depending on the status or country of the respondents. Recommendations for future research and observations for teacher training are discussed.